2021
DOI: 10.1186/s12711-021-00615-4
|View full text |Cite
|
Sign up to set email alerts
|

SNP panels for the estimation of dairy breed proportion and parentage assignment in African crossbred dairy cattle

Abstract: Background Understanding the relationship between genetic admixture and phenotypic performance is crucial for the optimization of crossbreeding programs. The use of small sets of informative ancestry markers can be a cost-effective option for the estimation of breed composition and for parentage assignment in situations where pedigree recording is difficult. The objectives of this study were to develop small single nucleotide polymorphism (SNP) panels that can accurately estimate the total dair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 41 publications
(50 reference statements)
2
16
0
1
Order By: Relevance
“…Previous studies have shown that 200–400 markers are sufficient to obtain accurate estimates of dairy breed proportions (Gebrehiwot et al., 2021; Strucken et al., 2017), and that only a negligible improvement in estimation accuracy was achieved with more than 500 markers. Therefore, we tested small panels of 100, 200, 300, 400 and 500 SNPs.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that 200–400 markers are sufficient to obtain accurate estimates of dairy breed proportions (Gebrehiwot et al., 2021; Strucken et al., 2017), and that only a negligible improvement in estimation accuracy was achieved with more than 500 markers. Therefore, we tested small panels of 100, 200, 300, 400 and 500 SNPs.…”
Section: Methodsmentioning
confidence: 99%
“…The distinction between B. taurus (EXO) and B. indicus (IND) can be achieved with relatively fewer markers compared to the distinction between B. taurus breeds (Gebrehiwot et al., 2021). To develop a panel that could distinguish between indicine and exotic as well as between Holstein‐Friesian and Jersey proportions, we created panels with different ratios of markers selected from both optimized panels for EXO versus IND and HF versus J.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most likely, this is due to the fact that this statistic can be easily adapted (e.g., global vs. pairwise) to make it suitable for the selection of markers for breed assignment. Regression on allele frequencies (He et al., 2018; Kuehn et al., 2011) and absolute allele frequency differences (Ding et al., 2011; Frkonja et al., 2012; Gebrehiwot et al., 2021; Hulsegge et al., 2013; Wilkinson et al., 2011) are other common methodologies for selection of markers for breed assignment. Several studies also used principal component analysis (PCA), based on different types of data input, to select the best SNP markers for discriminating breeds (Wilkinson et al., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported the results of paternity testing based on the number of OH, which is the exclusion-based approach, using genome-wide SNP markers genotyped by commercial chips in different cattle breeds (e.g. Calus et al, 2011;García-Ruiz et al, 2019;Gebrehiwot et al, 2021;Hayes, 2011;Purfield et al, 2016;Strucken et al, 2016Strucken et al, , 2017Wiggans et al, 2009). The likelihoodbased approach might be better in theory and therefore has greater accuracy, but computational costs are high especially when applied to large-scale data sets (Moore et al, 2019).…”
Section: Introductionmentioning
confidence: 99%